Redistribution of Iron and Titanium in High-Pressure Ultramafic Rocks - Crossley, R.; Evans, Katy; Reddy, S.; Lester, G. (Wiley-Blackwell Publishing, 2017)
© 2017. American Geophysical Union. The redox state of iron in high-pressure serpentinites, which host a significant proportion of Fe 3+ in subduction zones, can be used to provide an insight into iron cycling and constrain the composition of subduction zone fluids. In this study, we use oxide and silicate mineral textures, interpretation of mineral parageneses, mineral composition data, and whole rock geochemistry of high-pressure retrogressed ultramafic rocks from the Zermatt-Saas Zone to constrain the distribution of iron and titanium, and iron oxidation state. These data provide an insight on the oxidation state and composition of fluids at depth in subduction zones. Oxide minerals host the bulk of iron, particularly Fe 3+ . The increase in mode of magnetite and observation of magnetite within antigorite veins in the investigated ultramafic samples during initial retrogression is most consistent with oxidation of existing iron within the samples during the infiltration of an oxidizing fluid since it is difficult to reconcile addition of Fe 3+ with the known limited solubility of this species. However, high Ti contents are not typical of serpentinites and also cannot be accounted for by simple mixing of a depleted mantle protolith with the nearby Allalin gabbro. Titanium-rich phases coincide with prograde metamorphism and initial exhumation, implying the early seafloor and/or prograde addition and late mobilization of Ti. If Ti addition has occurred, then the introduction of Fe 3+ , also generally considered to be immobile, cannot be disregarded. We explore possible transport vectors for Ti and Fe through mineral texture analysis.